Tester for blood pressure measurement systems. - Hernández López, V.; Bautista León, M. A.; Hernández Matos, E. (Revista Mexicana de Ingenieria Biomedica, 1991)
In this article we describe the design of a test equipment for blood pressure monitors that performs static and dynamic checks. The team is equipped with two basic functions: 1.- A system tester that includes the transducer. 2.- An electronic circuit tester.